Skills, Tasks and the Scarcity of Talent in a Global Economy - Michael Koch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper sets up a heterogeneous firms model, where production consists of a continuum of tasks that differ in complexity. Firms hire low-skilled and high-skilled workers to perform these tasks. How firms assign workers to tasks depends on factor prices for the two skill types and the productivity advantage of high-skilled workers in the performance of complex tasks. I study the firms assignment problem under two labor market regimes, which capture the polar cases of fully flexible wages and a binding minimum wage for low-skilled workers. Since the minimum wage lowers the skill premium, it reduces the range of tasks performed by high-skilled workers, which increases firm-level productivity and reduces the mass of active firms. Whereas trade does not affect the firm-internal assignment of workers to tasks, it reduces the range of tasks produced by high-skilled workers within firms and thereby lowers firm-level productivity, if low-skilled wages are fixed by a minimum wage. In this case trade leads to higher per-capita income for both skill types and thus to higher welfare in the open than in the closed economy, whereas inequality between the two skill types decreases.
Keywords: F12; F16; F10; 330